Hybrid Learning : Solusi Pembelajaran Bahasa di Era New-Normal - Lina Tri Astuty Beru Sembiring; Merry Rullyanti (Literary Criticism, 2021)
The times demand students to always adapt to learning media. IT-based learning media is an important part of the 21st century. On the other hand, we are entering a "new normal" order, which means the return to conditions that were originally home learning and now back to normal. Students are allowed to learn 50% or half of the number of students. Of course, it leaves questions for students, how to study well. Hybrid learning is a solution to student problems in this new normal era. However, is it believed that hybrid learning can work efficiently and increase learning motivation? To answer this question, research was carried out using a quasi-experimental methodology by creating two groups. Namely the experimental group and the control group. The experimental group was given hybrid learning while the control group was given online learning. The results of this study are that the average value of hybrid learning is higher than the average value of online learning. So that hybrid learning can be recommended for teachers in this new normal era. Keyword: Hybrid Learning, quasi-experimental, online learning